2017
DOI: 10.1521/aeap.2017.29.2.121
|View full text |Cite
|
Sign up to set email alerts
|

HIV Risk Reduction Interventions Among Substance-Abusing Reproductive-Age Women: A Systematic Review

Abstract: HIV/AIDS is one of the leading causes of death among reproductive-age women throughout the world, and substance abuse plays a major role in HIV infection. We conducted a systematic review, in accordance with the 2015 Preferred Items for Reporting Systematic Reviews and Meta-analysis tool, to assess HIV risk-reduction intervention studies among reproductive-age women who abuse substances. We initially identified 6,506 articles during our search and, after screening titles and abstracts, examining articles in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This overview identified meaningful improvements for the intervention group such as reducing HIV/AIDS risk behaviours, although of low quality of evidence. The reviews identified no significant differences between multi-section psychosocial interventions and standard education in reducing HIV risk behaviours (64,65).…”
Section: Interventions Targeted To Reduce Hiv/aids Risk Behavioursmentioning
confidence: 95%
“…This overview identified meaningful improvements for the intervention group such as reducing HIV/AIDS risk behaviours, although of low quality of evidence. The reviews identified no significant differences between multi-section psychosocial interventions and standard education in reducing HIV risk behaviours (64,65).…”
Section: Interventions Targeted To Reduce Hiv/aids Risk Behavioursmentioning
confidence: 95%
“…Substance abuse plays a major role in human immunodeficiency virus (HIV) infection transmission; approximately 29% of HIV-infected women contracted the virus through injecting drugs, and another 15% contracted it through sexual contact with an HIV-infected drug user. In 2017, an estimated 47% of new infections occurred among key populations and their partners [4,5]. Despite significant advances in the prevention of HIV/acquired immunodeficiency syndrome (AIDS) and hepatitis, injection drug use continues to contribute to new infections, both directly through the sharing of injection equipment, and indirectly through sexual transmission from injection drug use (IDU) to non-IDU sex partners [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant advances in the prevention of HIV/acquired immunodeficiency syndrome (AIDS) and hepatitis, injection drug use continues to contribute to new infections, both directly through the sharing of injection equipment, and indirectly through sexual transmission from injection drug use (IDU) to non-IDU sex partners [6][7][8][9]. The exchange of sex for drugs or money, another risk factor for HIV infection, is common among those who abuse drugs [5]. Risky sexual behaviours (RSBs) are highly prevalent among people with SRDs because being under the influence of a substance can disrupt the judgment of the individual, resulting in involvement in risky behaviours, particularly RSBs [10][11][12], and it often leads to adverse health outcomes [13] such as reduced or no condom use, an increased number of sexual partners -particularly when combined with illicit drugs and alcohol use -and sex with high-risk sexual partners, as well as exchanging sex for drugs or money, resulting in an increased risk of HIV and hepatitis B virus (HBV) infection [5,10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…To identify a potential scope of existing interventions to curb opioid crisis, an initial search was performed for an overarching research study (Canadian Institutes of Health Research [CIHR] grant #EOC-162067). Among others, this search revealed eighteen SRs [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] on OUAIs prevention. The identi ed literature was limited to the HCV and HIV prevention, treatment, or integrated care, and targeted population of persons who inject drugs only.…”
mentioning
confidence: 99%